2021
DOI: 10.7196/sajch.2021.v15i1.01743
|View full text |Cite
|
Sign up to set email alerts
|

Associations between arterial stiffness and cardiovascular disease risk factors among black South African children

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.Cardiovascular disease (CVD) is the leading cause of mortality and morbidity worldwide and is estimated to cause 17.3 million deaths per year. [1] CVD incidence is strongly associated with a set of conventional risk factors, which include increased waist circumference (WC), high body mass index (BMI), high systolic blood pressure (SBP), increased levels of low-density lipoprotein, high blood glucose levels, low levels of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In general, the functional capabilities of the cardiovascular system of 9-year-old students correspond to the average level (3 points) according to both the Robinson and Ruffier indices. These results are consistent with the findings of previous studies [3,8,30,31,32] that have shown that the functional capabilities of the cardiovascular system of children are generally at an average level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the functional capabilities of the cardiovascular system of 9-year-old students correspond to the average level (3 points) according to both the Robinson and Ruffier indices. These results are consistent with the findings of previous studies [3,8,30,31,32] that have shown that the functional capabilities of the cardiovascular system of children are generally at an average level.…”
Section: Discussionsupporting
confidence: 93%
“…Extensive research has established that physical activity not only enhances cardiovascular function but also reduces the risk of cardiovascular diseases later in life [1,2,3]. Studies have demonstrated that regular physical activity can improve cardiovascular function, mitigate the risk of cardiovascular disease, and contribute to overall health and well-being in children [4,5].…”
mentioning
confidence: 99%
“…However, very few studies assess the vascular function of children of African ancestry. A study in Kwa-Zulu Natal Province of South Africa shows that age and resting heart rate were positively associated with arterial stiffness among children aged 10-13 years old (149). Age could play an important role when assessing arterial stiffness (150).…”
Section: Vascular Dysfunction In Children and Adolescents Of African Ancestrymentioning
confidence: 99%
“…However, for a deeper understanding, it should be examined in conjunction with growth and maturation, given that body height at the transition from childhood to adolescence is documented to affect arterial stiffness. An association between resting heart rate and arterial stiffness in children is still lacking in the literature (149). A study conducted in the Eastern Cape Province, South Africa, among 6-to 9-year-old children finds that blood pressure parameters, such as mean arterial and diastolic blood pressure, increased with increasing PWV (151).…”
Section: Vascular Dysfunction In Children and Adolescents Of African Ancestrymentioning
confidence: 99%